2018
DOI: 10.1084/jem.20171922
|View full text |Cite
|
Sign up to set email alerts
|

TAK1 restricts spontaneous NLRP3 activation and cell death to control myeloid proliferation

Abstract: The NLRP3 inflammasome protects the host against microbial infections. In this study, Malireddi et al. demonstrate the critical role of TAK1 in restricting RIPK1 signaling to inhibit spontaneous NLRP3 inflammasome activation and cell death, which may be targeted for treatment of myeloid proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
203
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(216 citation statements)
references
References 68 publications
12
203
1
Order By: Relevance
“…In this issue, Malireddi and colleagues used a myeloid-specific TAK1 KO mouse to shed new light on a novel, antiinflammatory function of TAK1 in macrophages that may explain, at first sight, the paradoxical inflammatory findings. As previously demonstrated in other cell models, they found that TAK1 deletion or inhibition resulted in spontaneous death of the TAK1-deficient macrophages, mediated by enhanced RIP1 and RIP3 signaling (Malireddi et al, 2018). Strikingly, however, these cells also underwent spontaneous NLRP3 inflammasome activation in the absence of any exogenous signals.…”
Section: Tak1ng Control: Tak1 Restrains Nlrp3 Activationsupporting
confidence: 68%
“…In this issue, Malireddi and colleagues used a myeloid-specific TAK1 KO mouse to shed new light on a novel, antiinflammatory function of TAK1 in macrophages that may explain, at first sight, the paradoxical inflammatory findings. As previously demonstrated in other cell models, they found that TAK1 deletion or inhibition resulted in spontaneous death of the TAK1-deficient macrophages, mediated by enhanced RIP1 and RIP3 signaling (Malireddi et al, 2018). Strikingly, however, these cells also underwent spontaneous NLRP3 inflammasome activation in the absence of any exogenous signals.…”
Section: Tak1ng Control: Tak1 Restrains Nlrp3 Activationsupporting
confidence: 68%
“…TAK1 has been shown to be crucial for mediating inflammation through NF-kB activation in many cell types (21). Recent published studies have demonstrated that TAK1 is also essential to prevent cell death in macrophages, cancer cells, and ECs (27,28,32). In our studies, under basal conditions we did not observe endothelial cell death either in TAK1 knockdown ECs or in TAK1-null ECs.…”
Section: Discussionsupporting
confidence: 47%
“…In B cells, TAK1 is required for B cell development and activation of NF-κB and MAPK signaling in response to TLR ligands, and BCR stimuli (23)(24)(25); whereas TAK1 in neutrophils negatively regulates NF-κB and p38MAP kinase activation (26). A study using myeloid-specific TAK1 knockout mice showed that TAK1 restricts spontaneous NLRP3 inflammasome activation and thereby prevents cell death in macrophages (27). TAK1 also suppresses RIPK1-dependent melanoma cell death (28) and RIPK3-dependent endothelial necroptosis (29).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, a previous study exploring kinase inhibitors in the context of inflammasome signaling had also identified TAK1 kinase activity as an important facilitator of NLRP3 inflammasome activation (Gong et al, 2010). While these data would argue for TAK1 kinase activity as a potential drug target in the NLRP3 inflammasome pathway, it has to be noted that prolonged inhibition of TAK1 can result in the induction of lytic cell death in the context of pro-inflammatory signals (Malireddi et al, 2018). This, in turn, can lead to secondary activation of the NLRP3 inflammasome due to the perturbation of membrane integrity and associated K + efflux.…”
Section: Discussionmentioning
confidence: 99%